El control de la reproducción como resultado de decisiones seguras o riesgosas (2006)
ABSTRACT: to understand the couple´s process to achieve fertility control. Methodology: a quantitative survey carried in Medellín, Colombia. Seventeen men and twenty three women between 20 and 35 years, of different social stratus and educational levels, with more than a year marital relationship were interviewed. The methodology is supported on grounded theory. Results: the findings show how according to feminine and masculine significants the couples assume a fixed position facing reproduction. This deal with is a decision-taking process between risky and safe decisions. Accordingly some are continually “searching security” to avoid unwanted children while others are continually “taking risks” about an unwanted pregnancy. Discussion: the couple’s strategies to face reproduction are tainted by their interpretation of the gender norms. The security looking couples assume gender norms in a flexible way whereas the risk-taking couples have a rigid perception of the gender norms and the power relationships. Conclusions: the conclusion is that the masculine and feminine significants about how males and females should be influences their reproductive behavior. The couples´ contexts and significants about reproduction define their behavior in birth control. Accordingly it is fundamental to know the context and perceptions about reproduction if we want to provide education able to transform behavior.